2020
DOI: 10.1042/cs20200478
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 in the renin–angiotensin system

Abstract: In 2020 we are celebrating the 20th anniversary of the angiotensin-converting enzyme 2 (ACE2) discovery. This event was a landmark that shaped the way that we see the renin–angiotensin system (RAS) today. ACE2 is an important molecular hub that connects the RAS classical arm, formed mainly by the octapeptide angiotensin II (Ang II) and its receptor AT1, with the RAS alternative or protective arm, formed mainly by the heptapeptides Ang-(1-7) and alamandine, and their receptors, Mas and MrgD, respectively. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 129 publications
0
37
0
Order By: Relevance
“…Alternatively, Ang 1-7 can be generated by a preliminary cleavage of the decapeptide Ang I with the formation of Ang 1-9, followed by the removal of two additional amino acids by ACE. Ang 1-7 may also be formed directly from Ang I, following proteolytic cleavage by neprilysin, and other endopeptidases [3,22,23].…”
Section: The Ras: Counteracting Harmful and Protective Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, Ang 1-7 can be generated by a preliminary cleavage of the decapeptide Ang I with the formation of Ang 1-9, followed by the removal of two additional amino acids by ACE. Ang 1-7 may also be formed directly from Ang I, following proteolytic cleavage by neprilysin, and other endopeptidases [3,22,23].…”
Section: The Ras: Counteracting Harmful and Protective Pathwaysmentioning
confidence: 99%
“…As opposed to the hazardous consequences of Ang II/AT1R stimulation, both AT2R, activated by Ang II, and MasR, triggered and internalized by Ang-(1-7) [24], exert cGMPand NO-mediated vasodilation, diuresis and natriuresis (with the induction of natriuretic peptide [25]), and attenuate inflammation, oxidative stress, cell proliferation, apoptosis, and coagulation [3,7,22,26] (Figure 1). Furthermore, Patel et al, studying obese Zucker rats, found that MasR co-localizes with AT2R in proximal tubular cells, and that both are functionally interdependent in terms of stimulating NO and promoting diuretic/natriuretic responses [27].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 in the renin-angiotensin system (RAS) and the apelin system, respectively [16,17]. The modulations of the cardiovascular peptide hormone systems have profound effects on physiology and pathophysiology in several organs.…”
Section: Figure 1 Structure Of Human Ace2mentioning
confidence: 99%
“…One problem inherent in such re-assessment of the fragments is the choice of the peptides to study. BK-(1-9) is a substrate for carboxypeptidases (e.g., ACE and ACE2), aminopeptidases (e.g., aminopeptidase P) and endopeptidases (e.g., neutral endopeptidase, now neprilysin), thus generating many different cleavage products (Campbell, 2013;Verano-Braga et al , 2020). A general conclusion of BK-(1-9) metabolism is that its major proteolytic fragment is the BK-(1-8), which is acknowledged as the only biologically active BK peptide known to date, together with BK-(1-7) and BK-(1-5) that are regarded as biologically inert fragments (Kopylov et al , 2016;Semis et al , 2019).…”
Section: Introductionmentioning
confidence: 99%